2015
DOI: 10.1111/nmo.12648
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of the 13C‐acetate breath test for comparing gastric emptying of different liquid test meals: a validation study using magnetic resonance imaging

Abstract: Background 13C‐acetate breath testing (BT) is applied to assess and compare gastric emptying of liquid meals. Gastric half‐emptying times (t50) from BT show offsets compared to t50 values from γ‐scintigraphy and ultrasonography. Linear transformations have been proposed to correct these offsets. This investigation critically validates the BT for the assessment of liquid gastric emptying by using simultaneously recorded meal and total gastric content volume emptying data from magnetic resonance imaging (MRI). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Delayed gastric emptying is one of the causes of FD. Gastric emptying can be measured by several kinds of methods, such as gastric emptying scintigraphy, barium-sandwich emptying radiography, gastric emptying ultrasound and 13 C-acetate breath test [5,6,7]. The 13 C-acetate breath test is widely used for the indirect assessment of gastric emptying [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed gastric emptying is one of the causes of FD. Gastric emptying can be measured by several kinds of methods, such as gastric emptying scintigraphy, barium-sandwich emptying radiography, gastric emptying ultrasound and 13 C-acetate breath test [5,6,7]. The 13 C-acetate breath test is widely used for the indirect assessment of gastric emptying [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric emptying can be measured by several kinds of methods, such as gastric emptying scintigraphy, barium-sandwich emptying radiography, gastric emptying ultrasound and 13 C-acetate breath test [5,6,7]. The 13 C-acetate breath test is widely used for the indirect assessment of gastric emptying [5]. The advantage of 13 C-acetate breath test is that it is a simple and easy method, there is no exposure to radiation, and there is no need for specialized facilities [8].…”
Section: Introductionmentioning
confidence: 99%
“…The current study assessed GE over 90 minutes with both BT and MRI, whereas other studies kept collecting breath samples after finishing the MRI measurements . Our MRI measurements showed that at the end of the sampling time not all of the meal had emptied from the stomach.…”
Section: Discussionmentioning
confidence: 92%
“…This was measured by MRI and BT using 100 mg 13 C‐acetate. It was suggested that these differences were caused by dilution by gastric secretions and the composition of the meal . Accordingly, tracer interactions with fat components in a test meal have been shown to affect tracer absorption and subsequent excretion and thus tracer‐based estimates of GE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation